Inorganic Particle Synthesis via Macro and Microemulsions : a Micrometer to Nanometer Landscape - Ganguli, D. (Dibyendu) (Springer US : Imprint : Springer, 2003)
The present book deals with the most important features of macro-and microemulsions that control the synthesis of inorganic particles of tailored size and shape, followed by wide spectrum surveys of the various procedures as they have been developed by research groups across the world. The aim of this book is thus to open a showcase of basic information on the two chemical regimes and detailed accounts of inorganic particles synthesis using the derived protocols. The intended audience is persons or groups who are not only looking for a simple and focused introduction to these chemical regimes, but also accounts of various synthetic procedures to select from their individual programs. It is also meant for curious individuals who want to know about the basics of the science and the art behind the macro- and microemulsion-based synthesis, but do not find them in a single and simple volume. The significance of this book lies in the fact that it fills this small gap in the immensely large volume of literature on the science and technology of ordinary emulsions and microemulsions.